HUBUNGAN ANTARA TIME PRESSURE DENGAN UNSAFE ACTION SAAT TRANSIT CHECK PADA TEKNISI PESAWAT TERBANG - Fany Trissiana (Universitas Airlangga, 2018)
Aircraft technician is a high-risk job where the work has a high level of risk with high in time and work pressures that lead to errors in the work that can cause harm to the company and himself. This study aims to determine the relationship between time pressure and unsafe actions on aircraft engineers PT. X. This research is analytical observational with cross sectional design. The sample in this research is the aircraft technician workers at Unit Out Station Line Maintenance PT. X with 70 total respondents. Technique of collecting data by using questionnaire to know the description of time pressure and observation sheet to know the unsafe action done by aircraft technician. The results of this study indicate that the number of respondents who experienced time pressure as much as 35.7% and who did unsafe actions as much as 45.7%. From the statistical test shows that there is a relationship between time pressure and unsafe action with p value < 0.05. The p value of time pressure relation and insecurity p = 0.049. It is necessary to give strict sanctions if it finds the worker doing unsafe acts and conduct safe work-related training. In addition, review the number of workers so as not to burden the workers due to lack of manpower.Keywords: aircraft technician, time pressure, transit check, unsafe action